And sometimes, we say good night - Cheryl Green (Elsevier, 2022)
The evolution of life is that one day after we are born, we must say good night, and fall asleep and breath no more. The trepidation of death is more than the ceasing of lung, cardiac, and brain function; for the nurse who loses a nurse colleague, it is a farewell of a collegial relationship that developed in the process of healing others. The death of a nurse colleague is sacred.